Process Technology Of Fabrication NO2 Gas Sensor Devices With Active Layer In2O3 - Slamet Widodo (UNIVERSITAS SEBELAS MARET (UNS), 2014)
This paper discuss the design and fabrication of NO2 gas sensor based on metal oxide using thick film technology was described. The design of gas sensor is consisted of components, i.e. heater, electrode (interdigital fingers) and sensitive layer from In2O3 material. This sensor has been designed as multilayers with heater and both electrodes in one surface, in accordance with miniaturisation aspect, heat distribution and less consumption of energy from the sensor device. The heater and electrode were fabricated on alumina substrate (aluminum oxide/Al2O3) with silver paste. The In2O3 layer provides resistance change when it is exposed by NO2 gas. It indicates that this sensor device has a potency to be used as NO2 detector.